Remote sensing of temperature -A numerical experiment (MAUSAM, 1986)
Constrained linear inversion technique is shown to yield accurate and numerically stable solution subject to proper choice of constraint. Some selection rules for determining the suitable constraint parameters are discussed in light of the numerical experiment.